Inti (Hymenoptera: Eulophidae) a peculiar new genus from tropical America - Hansson, Christer (Zootaxa, 2010)
Inti gen. nov. (Hymenoptera: Eulophidae: Entedoninae), is described from Costa Rica and the Dominican Republic, and includes one new species, I. levis sp. nov. The new genus is characterized by four autapomorphies, and the possession of an additional 14 synapomorphies. Inti is compared to the Australian genus Horismenoides Girault with which it shares the most apomorphies, indicating a possible sister-group relationship. The relationship of Inti to the tribe Euderomphalini and to other groups in the subfamily is discussed briefly.